Promotion pressures of local leaders and real estate investments: China and leader heterogeneity - Zhuo Chen; Mingzhi Hu; Zhiyi Qiu (Journal of Risk and Financial Management, 2022)
Chinese local officials have strong incentives to stimulate economic growth in the pursuit of promotion. However, the connection between promotion pressure of local officials and investment in the real estate market has not been rigorously explored. By using the panel data of local leaders (municipal party secretaries or mayors) from 2002 to 2010, this paper investigates the correlations between local leaders' promotion pressures and growth in real estate investments. Empirical results show that local leaders' promotion pressures are significantly and positively correlated with the growth of the real estate market. Furthermore, the positive effect of promotion pressure on real estate development is significant if the leader is young or born locally, whereas this effect is insignificant if the leader is older or not a native. Our findings provide new evidence on how local leaders may strategically intervene in local economic activities.
Keywords: 650; China; local officials; promotion pressure; real estate investment